LANGUAGE DEATH AND PRESERVATION: STRATEGIES FOR ENDANGERED LANGUAGES - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article examines the phenomenon of language death and strategies for preserving endangered languages. It explores the sociolinguistic, cultural, and cognitive implications of language loss, emphasizing the erosion of cultural heritage, oral traditions, and indigenous knowledge systems. The study identifies the causes of language endangerment, including globalization, urbanization, colonial history, governmental language policies, and intergenerational transmission gaps. It also discusses methods of language preservation, such as documentation, revitalization programs, immersion schools, media promotion, and technological interventions. The article highlights the importance of community involvement, education, and supportive policies in sustaining linguistic diversity. Ultimately, it demonstrates that proactive strategies are essential to safeguard endangered languages, maintain cultural identity, and promote intercultural understanding in a globalized world.